ҚЫТАЙ ТІЛІНДЕГІ ТҰРАҚТЫ СӨЗ ТІРКЕСТЕРДІ АУДАРУ ЖОЛДАРЫ. - Қалиқан, Ә. (Journal of Oriental Studies, 2016)
Бұл мақалады қазақ тіліне аудару жолдарын айқын- дайтын зерттеу жұмысы арқылы екі халықтың сөздік құрамының ерекшеліктерімен танысып, сонымен қатар, қытай тілін үйренушілер үшін тіл байлығын кеңейтуге, қытай мәдениетін терең түсінуге мүмкіндік береді. Idioms is the crystallization of language development. Thinking it new, refined form, people with a strong sense of beauty. Primarily reflected in its brief to the expression of semantics. At the same time, it is often the sentence and the use of special materials and various figures of speech, A feast for the eyes produce their form of the language. Paper on the cultural differences between English and Chinese idioms of its three main translation, transliteration, translation, live translation.